Pendekatan Tes Diskret dalam Pembelajaran Bahasa Arab - Herdah; Firmansyah; Ali Rahman (IAIN PAREPARE, 2020)
The scope of the Arabic Language Test can be categorized into two, Arabic component tests and language skills tests. Language component tests can be grouped into comprehension tests and usage tests. The component language test include vocabulary and structure tests. While language skills tests include listening, reading, speaking, writing, dictation, cloze tests, and C-tests. The discrete approach in language testing is based on structural linguistic understanding which considers language as something that consists of parts arranged according to a certain structure. Discrete approach test is applied on the basis of conventional understanding of language which consists of four language skills and four components of language namely writing, reading, speaking, and listening skills.